STRATEGI GURU PAUD DALAM MENINGKATKAN KARAKTER MANDIRI ANAK DARI KELUARGA PEKERJA LEPAS DI KB AN NUR SUKOSARI KIDUL - Nur Diana Holidah, Fiky Amalia; M. Fadil Djamali; Eka Olivia Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of independence during early childhood is a fundamental aspect of socio-emotional growth that is strongly influenced by both family and school environments. However, children from freelance worker families often experience limited parental assistance due to irregular working hours, unstable income, and demanding physical labor, resulting in inadequate stimulation of independent behavior. This study aims to analyze early childhood teachers' strategies in fostering children's independence, identify the forms of independence developed after pedagogical stimulation, and examine the supporting and inhibiting factors encountered during the implementation of these strategies. This research employed a qualitative descriptive approach and case study, conducted at KB An Nur Sukosari Kidul, Bondowoso, Indonesia. The participants consisted of two teachers, forty children aged 3–6 years, and seven parents selected through purposive sampling. Data were collected through structured observations, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana, while data credibility was ensured through source and technique triangulation. The findings indicate that teachers implemented six integrated pedagogical strategies: environmental conditioning, structured habituation, teacher modeling, positive reinforcement, persuasive instructional guidance, and continuous communication with parents. These strategies contributed to significant improvements in children's physical independence, psychological confidence, and responsibility in daily classroom activities, despite the limitations of family support. Nevertheless, the effectiveness of these strategies was influenced by parental consistency, socioeconomic conditions, and the intensity of school-family collaboration.